Some New Postquantum Integral Inequalities. (6th November 2020) - Chu, Yu-Ming; Awan, Muhammad Uzair; Talib, Sadia; Iftikhar, Sabah; Riahi, Latifa
Abstract : The goal of this paper is to derive a new generalized postquantum integral identity. Using this new identity as an auxiliary result, we derive some new variants of integral inequalities using p, q -differentiable preinvex functions. We also point out some special cases of the obtained results which show that our results are quite unifying ones.